MOTIVASI PESERTA SENAM AEROBIK DI ERISTY MANAGEMENT KOTA SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Motivation to be studied by the researchers is the aspect of physiological needs , safety needs aspects , aspects of social needs , esteem needs aspects, and aspects of actualization needs. The approach used in this study uses a qualitative research approach which means it will explain a phenomenon that occurs in aerobics participants.Data collection methods used in this study is a questionnaire survey method, observation and documentation. Methods of data analysis using descriptive percentages. The results of the analysis of research data, the level of motivation of participants overall aerobic Eristy Management Semarang in 2013 are as follows : 1) the physiological aspect as much as 86 % or some 52 people with a very good category, 2) security aspect as much as 81 % or 49 people with the good category, 3) the social aspect as much as 76 % or 46 people with either category, 4) Aspects of the award as much as 76 % or 46 people with a good category, 5) Aspects of actualization as much as 76 % or 46 people with both categories . The conclusion is the motivation of participants in the aerobic exercise Eristy Management Semarang in 2013 is due to physiological needs, amounting to 86 % or 52 people. The aerobics participants have very high motivation to maintain a healthy body and fitness..